2011
DOI: 10.1016/j.resp.2011.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Airway inflammation and central respiratory control: Results from in vivo and in vitro neonatal rat

Abstract: In infants, respiratory infection elicits tachypnea. To begin to evaluate the role of brainstem cytokine expression in modulation of breathing pattern changes, we compared the pattern generated after endotracheal instillation of lipopolysaccharide (LPS) in in vivo rat pups to local pro-inflammatory cytokine injection in the nucleus tractus solitarius (nTS) in an in vitro en bloc brainstem spinal cord preparation. We hypothesized that both challenges would elicit similar changes in patterning of respiration. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 41 publications
1
22
0
Order By: Relevance
“…As IL-1β does not readily cross the blood brain barrier, a likely mechanism for the resultant apnea was thought to be IL-1β-induced activation of the cyclooxygenase-2 pathway and release of prostaglandin E2 which can cross the blood brain barrier with resultant respiratory depression (Hofstetter et al, 2007). Indeed, based upon data published from our group (Gresham et al, 2011) we have shown that both in vivo and in vitro rat models show changes in frequency of breathing rhythm in response to LPS or IL-1β. Our current data suggest that intrapulmonary or systemic infection actually stimulates IL-1β production from neurons within respiratory related regions of the brainstem.…”
Section: Discussionmentioning
confidence: 87%
“…As IL-1β does not readily cross the blood brain barrier, a likely mechanism for the resultant apnea was thought to be IL-1β-induced activation of the cyclooxygenase-2 pathway and release of prostaglandin E2 which can cross the blood brain barrier with resultant respiratory depression (Hofstetter et al, 2007). Indeed, based upon data published from our group (Gresham et al, 2011) we have shown that both in vivo and in vitro rat models show changes in frequency of breathing rhythm in response to LPS or IL-1β. Our current data suggest that intrapulmonary or systemic infection actually stimulates IL-1β production from neurons within respiratory related regions of the brainstem.…”
Section: Discussionmentioning
confidence: 87%
“…It is possible that microglial activation triggers the release of one or several inhibitory neuromodulators (Henry et al, 2009;Kaur et al, 2013;Lai and Todd 2006;Smith et al, 2013;Yang et al, 2013) that regulate the preB€ otC. Among the neuromodulators released by microglia are several inhibitors of respiratory rhythm generation (Aleksandrova et al, 2015;Gresham et al, 2011;Guerra et al, 1988;Kitterman et al, 1983;Olsson et al, 2003;Tai and Adamson, 2000;VanDam et al, 2008;), such as interleukins (Aleksandrova et al, 2015;Gresham et al, 2011;Henry et al, 2009;Kaur et al, 2013;Lai and Todd 2006;Olsson et al, 2003;Smith et al, 2013;Yang et al, 2013), prostaglandin E2 (Guerra et al, 1988;Kitterman et al, 1983;Tai and Adamson, 2000;Wang et al, 2011;Zhang et al, 2009), hydrogen peroxide (Garcia et al, 2011), adenosine (Lauro et al, 2010;VanDam et al, 2008;Zwicker et al, 2011) and glycine (Hayashi et al, 2006;Ren and Greer, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…How hypoxia and inflammation interact within the CNS is an interesting and emerging area of research, with important implications for the respiratory system and the clinic (Gresham et al . ; Jafri et al . ; Lorea‐Hernandez et al .…”
Section: Introductionmentioning
confidence: 99%
“…A commonly used approach to study inflammation is the use of lipopolysaccharide (LPS; Gresham et al . ; Balan et al . ; Master et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation